Junior high school students’ mathematical literacy in terms of mathematical self-efficacy - Fifi Khairun Nisa; Elly Arliani (Jurnal Elemen, 2023)
Mathematical literacy and self-efficacy are critical in learning, especially mathematics. In contrast to previous studies, which only describe mathematical literacy and self-efficacy, this study aims to describe the ability of mathematical literacy in terms of mathematical self-efficacy. This research was a survey research qualitative and quantitative approaches. The results of this study indicate that the mathematical literacy abilities of grade VIII students in junior high school in Yogyakarta with sample 436 students are in a low category and the mathematical self-efficacy in the medium category. The higher the students’ mathematical self-efficacy, the higher their mathematical literacy. Students with high mathematical self-efficacy also tend to keep their maximum effort because they have the confidence to solve math literacy questions. Students with medium mathematical self-efficacy tend to doubt their abilities when facing difficult mathematical literacy questions. Students with low mathematical self-efficacy tend not to be confident in solving them because they think they lack mathematical abilities. This research is expected to map the mathematical literacy abilities of junior high school students in Yogyakarta. Besides, it can make material for reflection in world education to improve it.